Pendayagunaan Kepuasan dan Suasana Kerja dalam Peningkatan Daya Saing Sekolah Swasta - Tampubolon, Hotner (Jurnal Simki Pedagogia, 2023)
This study aims to analyze the utilization of job satisfaction and work atmosphere in increasing the competitiveness of private schools. The research population is teachers in private schools in Jakarta. Data were collected through in-depth interviews and field observations, then analyzed using content analysis techniques. The results of the study show that there are factors that influence job satisfaction and work atmosphere in private schools, including effective communication, leadership support, a conducive work environment, and rewards for good performance. There are also differences in perceptions between teachers and administrative staff regarding some aspects of job satisfaction and work atmosphere. There are differences between expectations and performance in several aspects of job satisfaction and work atmosphere in private schools. This demonstrates the potential for improving performance and improving the unsatisfactory state of affairs in terms of job satisfaction and working atmosphere in private schools. This finding is consistent with relevant previous research results. Therefore, it is recommended that private schools pay attention to the factors that affect job satisfaction and work atmosphere, and make efforts to improve performance and meet the expectations of teachers and administrative staff in order to increase the competitiveness of schools.